2015
DOI: 10.1002/macp.201400454
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Chain‐End‐Functionalized Polyethylenes via Thiol‐ene Click Chemistry

Abstract: Chain‐end‐functionalized polyethylenes (Cef‐PEs: PESSH (Cef1), PESfurfuryl (Cef2), PESNH2 (Cef4), PESNH2•HCl (Cef5), PESCOONa (Cef6), PESCHA(Cef7), PESSO3Na (Cef8), PESOH (Cef9) and PESCOOH (Cef10)) are synthesized by thiol‐ene addition of vinyl‐terminated polyethylene (v‐PE) with 1,2‐ethanedithiol, furfurylmercaptan, cysteamine, cysteamine hydrochloride, sodium thioglycolate, L‐cysteine hydrochloride, sodium 2‐mercaptoethanesulfonate, mercaptoethanol, and thioglycolic acid, respectively. PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Besides, the peaks at 2706, 1635, 1464, and 1147 cm −1 were assigned to the stretching vibrations of CH, CO, imidazole ring, and the bending vibration of NH, respectively, confirming the existence of histidine on the surface of MES‐Au NCs. Furthermore, peaks at 1211 and 1180 cm −1 could be ascribed to the stretching vibration of SO, demonstrating the existence of terminal sulfonic group and confirming the formation of MES‐conjugated MES‐Au NCs . Obviously, the SH stretching vibration of MES at 2571 cm −1 disappeared after the formation of MES‐Au NCs, suggesting the combination of MES with Au NCs via the formation of AuS bond .…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Besides, the peaks at 2706, 1635, 1464, and 1147 cm −1 were assigned to the stretching vibrations of CH, CO, imidazole ring, and the bending vibration of NH, respectively, confirming the existence of histidine on the surface of MES‐Au NCs. Furthermore, peaks at 1211 and 1180 cm −1 could be ascribed to the stretching vibration of SO, demonstrating the existence of terminal sulfonic group and confirming the formation of MES‐conjugated MES‐Au NCs . Obviously, the SH stretching vibration of MES at 2571 cm −1 disappeared after the formation of MES‐Au NCs, suggesting the combination of MES with Au NCs via the formation of AuS bond .…”
Section: Resultsmentioning
confidence: 76%
“…In the Au4f spectrum of His‐Au NCs and MES‐Au NCs (Figure S3c, Supporting Information), after partial replacement of histidine with MES, the peak of Au4f 7/2 shifted from 84.7 to 84.1 eV and the peak of Au4f 5/2 moved from 88.5 to 87.7 eV causing the transformation of the binding energy of Au4f . In Figure S3d (Supporting Information), no S2p was detected in His‐Au NCs, and the peaks in the S2p spectrum of MES‐Au NCs at 163.2 and 167.7 eV should be ascribed to the sulfur from the sulfhydryl group and sulfonate group, demonstrating the successful formation of MES‐Au NCs …”
Section: Resultsmentioning
confidence: 99%
“…Two equivalents of dithiol were used to avoid formation of undesired dimer 2 that is typical for equimolar reagent ratio ( Figure S2). While others have shown that functional thiols can be attached to polyolefin oligomers with thiol-ene thermal chemistry [34], in our hands the photochemical approach described by Storey worked better [35]. Photoinitiation with 365 nm UV light of the PIB-alkene in 8 h afforded a mixture of the desired compound 1 and bis-adduct 2 ( Figure S2).…”
Section: Synthesis Of Polymer-supported Sequestrantmentioning
confidence: 70%
“…Both the spectra of MES-Au NCs and MES showed the stretching vibrations of O]S]O at 1251 and 1179 cm À1 , strongly suggesting that MES anchors on the surface of Au NCs through the sulfur atom and Au atom by the formation of Au-S bond. 34,35 Meanwhile, both gold clusters exhibited the characteristic IR bands of imidazole ring (imidazole stretches; 1464 cm À1 ) of histidine, 36 conrming the partial replacement of His-ligands on the surfaces of His-Au NCs by MES. The ligand exchange could be further veried by Xray photoelectron spectroscopy (XPS).…”
Section: Resultsmentioning
confidence: 99%